Characteristics of Gut Microbiota in Female Patients with Diabetic Microvascular Complications - Shan Gao; Li-hua Zhao; Xue Tian; Mo-wei Kong; Jian-qiu He; Xiao-chun Ge; Xiao-yan Liu; Zeng-bin Feng; Yu Gao (Journal of Diabetes Research)
Objective. To explore the characteristics and analyze the gut microbiota in female patients with diabetic microvascular complications (DMC). Methods. Thirty-seven female patients with type 2 diabetes mellitus (T2DM) were included in the study. These patients were divided into DM group with microvascular complications (T2DM-MC, n=17) and no microvascular complications group (T2DM-0, n=20). Patients in the microvascular group presented with the involvement of at least one of the following: kidney, retinal, or peripheral nerves. Using real-time fluorescence quantitative polymerase chain reaction, fecal samples from the two groups were tested for Bacteroides, Prevotella, Bifidobacterium spp, Lactobacillus, Faecalibacterium prausnitzii, Enterococcus spp, Eubacterium rectale, Veillonellaceae, Clostridium leptum, and Roseburia inulinivorans. Levels of fasting and 2 h postprandial blood glucose, glycosylated hemoglobin (HbA1c), lipids, and creatinine were determined to explore the correlation between gut microbiota and blood sugar. Mann–Whitney U test was used to analyze the differences between the two groups. Spearman correlation analysis was used to determine the correlation between gut microbiota and blood glucose. Multifactor logistic regression was used to analyze the risk factors for DMC. Results. The HbA1c levels in the T2DM-MC group were higher than those in the T2DM-0 group. The abundances of Bacteroides and Enterococcus spp in the T2DM-MC group were higher than that in the T2DM-0 group. The abundances of Bacteroides and Enterococcus spp in the T2DM-MC group were lower than that in the T2DM-0 group. Spearman’s correlation analysis showed that Bacteroides, Prevotella, Lactobacillus, C. leptum, and R. inulinivorans were related to the levels of HbA1c or blood glucose (p<0.05). Logistic regression analysis showed that after adjusting for confounding factors such as age, body mass index, family history, HbA1c, hypertension, dyslipidemia, and creatinine, Bacteroides remained an independent risk factor in female patients with DMC. Conclusion. Gut microbiota is related to blood glucose levels. Female patients with DMC experience gut microbiota disorders. The abundances of Bacteroidesare related to DMC, and the abundances of intestinal flora may affect the blood sugar levels of the body.